3-(1,2,3-Triazol-4-yl)-β-Carbolines and 3-(1H-Tetrazol-5-yl)-β-Carbolines: Synthesis and Evaluation as Anticancer Agents - João L. P. Ribeiro; Joana B. Loureiro; Susana M. M. Lopes; Lucília Saraiva; Teresa M. V. D. Pinho e Melo (Pharmaceuticals, 2022)
Herein, the synthesis and anticancer activity evaluation of a series of novel β-carbolines is reported. The reactivity of nitrosoalkenes towards indole was explored for the synthesis of novel tryptophan analogs where the carboxylic acid was replaced by a triazole moiety. This tryptamine was used in the synthesis of 3-(1,2,3-triazol-4-yl)-β-carbolines via Pictet–Spengler condensation followed by an oxidative step. A library of compounds, including the novel 3-(1,2,3-triazol-4-yl)-β-carbolines as well as methyl β-carboline-3-carboxylate and 3-tetrazolyl-β-carboline derivatives, was evaluated for their antiproliferative activity against colorectal cancer cell lines. The 3-(1H-tetrazol-5-yl)-β-carbolines stood out as the most active compounds, with values of half-maximal inhibitory concentration (IC50) ranging from 3.3 µM to 9.6 µM against colorectal adenocarcinoma HCT116 and HT29 cell lines. The results also revealed a mechanism of action independent of the p53 pathway. Further studies with the 3-tetrazolyl-β-carboline derivative, which showed high selectivity for cancer cells, revealed IC50 values below 8 μM against pancreatic adenocarcinoma PANC-1, melanoma A375, hepatocarcinoma HEPG2, and breast adenocarcinoma MCF-7 cell lines. Collectively, this work discloses the 3-tetrazolyl-β-carboline derivative as a promising anticancer agent worthy of being further explored in future works.